Flavonoid glycosides from Dendrophthoe pentandra L. and isoflavonoid glycosides from Derris scandens benth - Yaowapa Sukpondma (Prince of Songkla University, 2020)
Thesis (M.Sc., Organic Chemistry)--Prince of Songkla University, 2000